(untitled) (Boletín de la Sociedad Argentina de Botánica, 2013)
Summary: On the presence of Amaranthus palmeri (Amaranthaceae) in Argentina. Amaranthus palmeri, a species native from USA and Mexico, is cited for the first time for the Argentinean adventitious flora mainly in the Córdoba province and also in San Luis and La Pampa provinces. The species is described and illustrated and their geographical distribution is mentioned. Key words: Amaranthus palmeri, Central Argentina, adventitious flora. Resumen: Amaranthus palmeri, especie nativa de Estados Unidos de Norte América y México, se cita por primera vez para la flora adventicia argentina sobre la base de ejemplares coleccionados principalmente en la provincia de Córdoba, además de San Luis y La Pampa. Se describe e ilustra la especie y se menciona su distribución geográfica. Palabras clave: Amaranthus palmeri, Argentina central, flora adventicia.